CURRENT VIEWS ON THE COURSE OF ACUTE STENOSING LARYNGOTRACHEITIS - Karimova L.A.; Kudratova Z. E. (Web of Journals Publishing, 2024)
Acute stenotic laryngotracheitis (croup) is the most frequent cause of acute upper airway obstruction in young children.
Keywords: acute stenotic laryngotracheitis, acute respiratory viral infection.